Flipped Classroom Teaching System Design under the Background of Subject Reform Based on Information Technology - Wang, Yang; Tong, Wuning; Lv, Qingli; Luo, Yu; Wei, Nian (Journal of physics. Conference series, 2021)
With the rapid development of modern information technology, some traditional teaching models in colleges and universities will not be able to adapt to the pace of change. The new teaching model flipped classroom not only meets the requirements of our country’s new curriculum reform, but also allows students to reduce the burden of learning after class, and achieve the best of both worlds. The purpose of this article is to study the design of the flipped classroom teaching system under the background of subject reform based on information technology. This article adopts literature research method, survey research method and action research method to carry out research. This article summarizes the flipped classroom teaching mode and practical cases through a literature review of relevant domestic and foreign literature. This article proposes how schools and teachers should respond to the development of information technology and the development trend of “flipped classroom” under the current situation, and provide certain guiding suggestions for future classroom teaching reforms. This article selects two classes of teachers and students in a university in this city as the research objects, investigates the current teaching status of the curriculum, summarizes and analyzes the characteristics and problems, and draws on the results of existing practical research to initially build a flipped classroom suitable for this teaching practice Model, and based on this model, select the content, carry out the teaching design and practical experiment of the flipped classroom, and finally this article carefully summarizes and reflects on the practice. The survey results show that. 85.45% of students find it helpful to increase the communication activities between teachers and students and between students in the classroom, and students can gain from the exchange and cooperation.